Electromagnetic Transients of Power Electronics Systems - Zhao, Zhengming; Yuan, Liqiang; Bai, Hua; Lu, Ting (Springer Nature Singapore : Imprint: Springer, 2019)
This book discusses topics related to power electronics, especially electromagnetic transient analysis and control of high-power electronics conversion. It focuses on the re-evaluation of power electronics, transient analysis and modeling, device-based system-safe operating area, and energy balance-based control methods, and presenting, for the first time, numerous experimental results for the transient process of various real-world converters. The book systematically presents both theoretical analysis and practical applications. The first chapter discusses the structure and attributes of power electronics systems, highlighting the analysis and synthesis, while the second chapter explores the transient process and modeling for power electronics systems. The transient features of power devices at switching-on/off, transient conversion circuit with stray parameters and device-based system-safe operating area are described in the subsequent three chapters. The book also examinesthe measurement of transient processes, electromagnetic pulses and their series, as well as high-performance, closed-loop control, and expounds the basic principles and method of the energy-balanced control strategy. Lastly, it introduces the applications of transient analysis of typical power electronics systems. The book is valuable as a textbook for college students, and as a reference resource for electrical engineers as well as anyone working in the field of high-power electronics system. .